Music education in the Middle Ages and the Renaissance - Murray, Russell Eugene; Weiss, Susan Forscher; Cyrus, Cynthia J. (Publications of the Early Music Institute., 2010)
What were the methods and educational philosophies of music teachers in the Middle Ages and the Renaissance? What did students study? What were the motivations of teacher and student? Contributors to this volume address these topics and other -- including gender, social status, and the role of the Church -- to better understand the identities of music teachers and students from 650 to 1650 in Western Europe. This volume provides an expansive view of the beginnings of music pedagogy, and shows how the act.